Early population-based outcomes of infants born with congenital diaphragmatic hernia. Issue 6 (4th January 2018) - Long, Anna-May; Bunch, Kathryn J; Knight, Marian; Kurinczuk, Jennifer J; Losty, Paul D
Abstract : Purpose: This study aims to describe short-term outcomes of live-born infants with congenital diaphragmatic hernia (CDH) and to identify prognostic factors associated with early mortality. Design: A prospective population cohort study was undertaken between April 2009 and September 2010, collecting data on live-born infants with CDH from all 28 paediatric surgical centres in the UK and Ireland using an established surgical surveillance system. Management and outcomes are described. Prognostic factors associated with death before surgery are explored. Results: Two hundred and nineteen live-born infants with CDH were reported within the data collection period. There were 1.5 times more boys than girls (n=133, 61%). Thirty-five infants (16%) died without an operation. This adverse outcome was associated with female sex (adjusted OR (aOR) 3.96, 95% CI 1.66 to 9.47), prenatal diagnosis (aOR 4.99, 95% CI 1.31 to 18.98), and the need for physiological support in the form of inotropes (aOR 9.96, 95% CI 1.19 to 83.25) or pulmonary vasodilators (aOR 4.09, 95% CI 1.53 to 10.93). Significant variation in practice existed among centres, and some therapies potentially detrimental to infant outcomes were used, including pulmonary surfactant in 45 antenatally diagnosed infants (34%). Utilisation of extracorporeal membrane oxygenation was very low compared with published international studies (n=9/219, 4%). Postoperative 30-day survival was 98% for 182 infants with CDH who were adequately physiologically stabilised and underwent surgery. Conclusion: This is the first British Isles population-based study reporting outcome metrics for infants born with CDH. 16% of babies did not survive to undergo surgery. Factors associated with poor outcome included female sex and prenatal diagnosis. Early postoperative survival in those who underwent surgical repair was excellent.